Predictive modelling of creep crack initiation and growth using Extended Finite Element Method (XFEM) - Meor Iqram Meor Ahmad; Mohd Anas Mohd Sabri; Mohd Faizal Mat Tahir; Nur Azam Abdullah (Fracture and Structural Integrity)
In this study, a numerical strategy for predictive modelling of creep in tension tests for the rectangular plate with a single crack and CT-specimen based on the extended finite element method (XFEM) will be described in detail. A model of creep fracture initiation and creep crack growth (CCG) is developed, while the XFEM is employed to spots located inside the finite element for the purpose of predicting crack potential and propagation. In order to characterize the creep fracture initiation, identification of C(t)-integral formula is conducted. In addition, XFEM and analytical solutions are also analyzed to look at the connection of C(t)-integral with time for a rectangular plate with a single crack under plane stress conditions. An illustration showing the sequence of stress distribution and displacement contour plots are also being presented. The stresses and displacements spread throughout the crack path have also been determined using CT-specimens. In addition, the creep cracks growth length with normalized time and the creep crack growth rate with the C(t)-integral are predicted to be related, indicating that the numerical results are in good accord with the experimental results.